Condition of teaching the Ukrainian language in secondary schools of the Crimean Autonomous Republic (Pedagogy of Higher and Secondary Education, 2013)
Kartavaya Y. K. Condition of teaching the Ukrainian language in secondary schools of the Crimean Autonomous Republic.The article outlines the modern state of teaching the Ukrainian language in secondary schools of the Crimean Autonomous Republic, analyzes the normative base and finds out major tendencies of raising the level of teaching the Ukrainian language by the teachers-philologists.
Keywords: teaching the Ukrainian language; secondary schools; raising the level of teaching; teachers-philologists